The Potential of Young Dates (Phoenix dactylifera) as an Agent in Supporting the Oogenesis Process: A Systematic Analysis - Novida Ariani (International Journal of Integrative Sciences, 2024)
This study examines the potential of young dates (Phoenix dactylifera) as a nutritional agent in supporting the oogenesis process, which is an important aspect of women's reproductive health. The introduction identifies that infertility is a global health problem affecting 10-15% of couples in Indonesia, and there is an urgent need for an alternative approach to infertility treatment. Young dates, which are known to be rich in bioactive compounds such as antioxidants and essential nutrients, have the potential to improve egg quality and support reproductive health. The method used in this study uses a systematic literature review approach by analyzing 557 articles from various databases. Selection was carried out based on strict inclusion and exclusion criteria, resulting in 9 relevant articles for further analysis. This process follows PRISMA and JBI guidelines to ensure the validity and reliability of the data. The results showed that young dates had a positive effect on hormonal balance, increased levels of FSH and LH hormones, and improved ovarian structure in animal models. Research has also found that young dates function as antioxidants that can protect reproductive cells from oxidative damage, as well as increase the number of ovarian follicles. The discussion in this study emphasizes the importance of young dates in improving the oogenesis process and overall female reproductive health. The study concluded that young dates may be a promising herbal therapy for improving female fertility, with recommendations for further research to understand the specific mechanisms underlying the effects. The results of this study are expected to contribute to the development of alternative treatment strategies for infertility problems in the future.